ความคาดหวังและความพึงพอใจของผู้ประกอบการวิสาหกิจขนาดกลางและขนาดย่อมต่อบริการสำนักงาน บัญชีในจังหวัดเชียงใหม่ - จิตติพร พูนสิน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The independent study is purposed to study the expectation and the satisfaction of small and medium enterprise entrepreneurs toward services of accounting firms in Chiang Mai province. The expectation and the satisfaction of accounting firms toward services render to entrepreneurs then compare the differences between the expectation and the satisfaction of entrepreneurs and accounting firms. The study has considered the expectation and the satisfaction by 3 aspects as the competitive differentiation, the service quality and the productivity. The data have been collected by do questionnaires with the entrepreneurs 385 samples and the accounting firms 133 sample.